1998
DOI: 10.1049/ip-gtd:19982183
|View full text |Cite
|
Sign up to set email alerts
|

Model-based analysis of protection system performance

Abstract: Following a power system fault, protection engineers have to analyse the protection scheme activity to ensure correct operation. To aid them in this task, data gathering systems are increasingly being fitted to power systems. However, during extreme operating conditions, the volume of data made available by these systems can be overwhelming. To help overcome this, knowledge-based systems have been developed and installed at ScottishPower's corporate headquarters to extract the relevant `information' from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 3 publications
0
12
0
1
Order By: Relevance
“…In fact, multiplying by -1 the fourth column in mod (11), the same value of syndrome is reached. Vice versa transition faults aren't present because the error syndrome is equal to 0.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact, multiplying by -1 the fourth column in mod (11), the same value of syndrome is reached. Vice versa transition faults aren't present because the error syndrome is equal to 0.…”
Section: Resultsmentioning
confidence: 88%
“…In [9][10] other two examples of MAS technology was shown, highlighting the flexibility and the extensibility it offers. Knowledgebased systems to extract the relevant information from SCADA system data had been presented in [11]. Regarding the second topic, in [12] an integrate scheme to study power system vulnerability in presence of protection failures was considered and a reliability system based on stochastic properties was tested.…”
Section: Introductionmentioning
confidence: 99%
“…Using MBR techniques this process can be automated to validate the performance of entire protection schemes as well as just the relays [7], [8], such as the protection for the feeder shown in Fig. 2.…”
Section: ) Transient and Dynamic Modelsmentioning
confidence: 99%
“…Nevertheless, a number of prototype systems have been developed which perform temporal MBD. A review of these systems can be found in [8] and [13]. In general, these systems have an underlying dependency on the type of models they employ, tying the developer to using a particular modeling formalism which is often related to the way time is represented.…”
Section: A Dealing With Dynamics and Temporal Diagnosismentioning
confidence: 99%
“…In the PEDA system fault diagnosis is performed by a sequential application of a Knowledge-Based System (KBS), which inclusion as an agent is described in [7], followed by a Model-Based System (MBS) described in [8]. The KBS and MBS were developed to perform independent tasks.…”
Section: Related Workmentioning
confidence: 99%